A potent candicidal peptide designed based on an encrypted peptide from a proteinase inhibitor - Almeida, Luís Henrique de Oliveira (2024)
Antimicrobial peptides (AMP) represent an alternative in the treatment of fungal infections associated with countless deaths. Here, we report a new AMP, named KWI-19, which was designed based on a peptide encrypted in the sequence of an Inga laurina Kunitz-type inhibitor (ILTI). KWI-19 inhibited the growth of Candida species and acted as a fungicidal agent from 2.5 to 20 μmol L−1, also showing synergistic activity with amphotericin B. Kinetic assays showed that KWI-19 killed Candida tropicalis cells within 60 min. We also report the membrane-associated mechanisms of action of KWI-19 and its interaction with ergosterol. KWI-19 was also characterized as a potent antibiofilm peptide, with activity against C. tropicalis. Finally, non-toxicity was reported against Galleria mellonella larvae, thus strengthening the interest in all the bioactivities mentioned above. This study extends our knowledge on how AMPs can be engineered from peptides encrypted in larger proteins and their potential as candicidal agents.